Ethical issues in digital technologies - Aude Schoentgen; Laura Wilkinson (International Telecommunications Society (ITS), 2021)
The paper explores how ethical frameworks and concerns arise within digital technologies and examines the implementation of ethics by governments and private companies. It concludes by proposing a forward-looking approach and identifying potential challenges to implement ethics within the design and use of digital technologies.
Keywords: 330